Faktor-Faktor yang Mempengaruhi Intensi Masyarakat Untuk Mengikuti Vaksinasi Covid-19 Dosis Lengkap di Kota Makassar - Risman Harnas; Anshar Saud; Muh. Akbar Bahar (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2024)
The control of the COVID-19 pandemic is influenced by the effective acceptance of vaccines. This study aims to identify the factors affecting the willingness of the public to receive the complete dose of COVID-19 vaccine in the city of Makassar. A cross-sectional research approach was employed, utilizing a questionnaire consisting of demographic information, perceptions of the severity and vulnerability to COVID-19, as well as barriers and benefits of COVID-19 vaccination, which were distributed online in Makassar City. Multivariate logistic regression analysis was used to identify independent factors influencing the intention of the public to receive the full dose (two doses) of the vaccine. A total of 310 respondents participated in this study. Respondents who perceived a high level of disease severity (aOR= 3.39; 95% CI: 1.41 – 8.14) had a higher likelihood of receiving full COVID-19 vaccination, while respondents with a perception of high access barriers to vaccination had a lower likelihood of receiving full COVID-19 vaccination (aOR= 0.18; 95% CI: 0.07 – 0.45). In this study, the intention to accept full COVID-19 vaccination was influenced by perceptions of disease severity and perceived access barriers to vaccination. The implementation of the COVID-19 immunization program by healthcare providers and local governments should incorporate various vaccination education strategies tailored to patients' health beliefs.